Cottonseed Oil Protects Against Intestinal Inflammation in Dextran Sodium Sulfate-Induced Inflammatory Bowel Disease - Park, Jin-Sil; Choi, JeongWon; Hwang, Sun-Hee; Kim, Jae-Kyung; Kim, Eun-Kyung; Lee, Seon-Young; Lee, Bo-In; Park, Sung-Hwan; Cho, Mi-La (Journal of medicinal food, 2019)
Dietary products may protect against inflammatory bowel disease (IBD) through mechanisms such as forming gut microbiota structures and providing substrates for microbial metabolism. Recently, many studies have been conducted on diets that potentially alleviate or suppress IBD development. To assess the efficacy of dietary oils in treating IBD, we examined the protective effects of olive oil, coconut oil, corn oil, and cottonseed oil in a dextran sodium sulfate (DSS)-induced colitis mouse model. Treatment with cottonseed oil or corn oil ameliorated the severity of DSS-induced colitis, alleviating weight loss and preventing the shortening of the intestine. Moreover, cottonseed oil or corn oil treatment significantly reduced the expression of inflammatory cytokines such as tumor necrosis factor- , interleukin (IL)-1 , IL-6, and IL-17, as well as the expression of oxidative stress markers, including 8-hydroxyguanosine and nitrotyrosine in colon sections, compared with vehicle treatment. Cottonseed oil treatment inhibited intestinal fibrosis by reducing the expression of -smooth muscle actin and type I collagen, compared with vehicle treatment in mice with DSS-induced colitis. Cottonseed oil protects against intestinal inflammation and the development of intestinal fibrosis by reducing inflammatory cytokines and oxidative stress markers, and may therefore be useful as a dietary product with therapeutic benefits for IBD.